Experimental investigation of sorption characteristics of capturing carbon dioxide into piperazine activated aqueous 2-amino-2-methyl-1-propanol solution in a packed column. (January 2016) - Khan, Anoar Ali; Halder, G.N.; Saha, A.K.
Highlights: Experiments were conducted in a packed bed using flue gas from a coal fire boiler. Regeneration efficiency was highest using AMP/PZ blend of 28/2 compared to 20/10. Reboiler heat duty was lowest in case of less (2 wt%) PZ concentration of (AMP + PZ). Experimental absorption data plotted with RSM-fitted data show a superb agreement. Regeneration efficiency of each blended amine compared with 30% MEA. Abstract: Gradual increase in concentration of CO2 in the atmosphere and its potential threat to the global climate has become the matter of widespread anxiety and significant research over the last few decades in order to find out the promising techniques for CO2 capture. The present study investigates a post-combustion technique of capturing CO2 from flue gas using aqueous amine blend of 2-amino-2-methyl-1-propanol (AMP) and piperazine (PZ). The absorption experiments have been performed in a packed column over the temperature range of 298–308 K and the CO2 partial pressure range of 10–15 kPa. CO2 absorption characteristics are examined with process variables viz. different solvent blend (wt% AMP + wt% PZ), gas flow rate, absorbent flow rate and different CO2 partial pressures. Piperazine is used mainly as reaction rate activator with a concentration range of 2–10 wt% maintaining the total amine concentration of 30 wt%. The regeneration performances of amine blend are studied over the temperature range of 368–383 K. The specific rate of absorption of different (AMP + PZ) blends, CO2 loading capacity of individual blends after absorption performance and percentage of CO2 absorbed have been examined. The specific rate of absorption for the four (AMP + PZ) blends have been found to be (14.6–26.8) × 10 −6 kmol m −2 s −1 . The maximum percentage of CO2 absorbed has been estimated to be 99.63% when the PZ concentration is maximum i.e. 10 wt% in the blend. The highest CO2 loading capacity has been observed to be 0.978 for the case of maximum PZ contribution in the blend solvent such as 10 wt%. Regeneration efficiencies of individual blend and the residual CO2 after stripping are studied. The regeneration efficiency of every individual amine blend is within the range of 90.93–98.93% and the maximum efficiency of 98.93% is observed for the case of highest AMP contribution in the (AMP + PZ) blend i.e. 28 wt% with addition of this blend also has the better regeneration performance which is represented as residual CO2 (0.026 moles per mole of amine blend) left in the regenerated amine blend. The cyclic CO2 loading capacity ranges from 0.858 to 0.978 moles of CO2 for entire four aqueous amine blends as compared to 30 wt% MEA which ranges from 0.405 to 0.524 moles of CO2 per mole of amine. The reboiler heat duty requirement to regenerate the CO2 rich aqueous amine solvent has been estimated for entire four different (AMP + PZ) blends and found to be within the range of 3.4–4.8 MJ/kg CO2 as compared to 30 wt% MEA which has the range of 3.6–4.5 MJ/kg CO2 . The experimental rate data are compared with the model predicted rate data and the parity plot shows an excellent agreement with the experimental results. Hence, sorption of CO2 into piperazine activated aqueous 2-amino-2-methyl-1-propanol solution in a packed bed column could be an efficient technique of entrapping CO2 from flue gas.